Characterization and pathogenicity of a novel avian nephritis virus isolated in China. Issue 1 (2nd January 2022) - Yin, Lijuan; Zhou, Qi; Huang, Jianfei; Mai, Kaijie; Yan, Zhuanqiang; Wei, Xiaona; Shen, Hanqin; Li, Qunhui; Chen, Li; Zhou, Qingfeng
ABSTRACT : Avian nephritis virus infections of chicken flocks cause enteric and kidney disease, uneven growth, and runting stunting syndrome, leading to economic losses in the poultry industry. In this study, one ANV strain, designated as AH202017, was isolated from a diseased broiler flock in Anhui province, China, in 2020. Virus production in LMH cell culture was confirmed by real-time RT–PCR and immunofluorescence assay. The complete genome sequencing analysis indicated that AH202017 shares 77.5–85.5% identity with 12 reference strains in GenBank. Phylogenetic analysis of the capsid protein revealed that AH202017 is more closely related to VIC-6a/Australia/2014 belonging to ANV genotype 2. However, the phylogenetic tree, based on the ORF1a protein and ORF1b protein, indicated that AH202017 manifests a close relationship with GXJL815/China/2017 belonging to genotype 8. In infection experiments, four infected chickens showed depression and one chicken died at 6 days post-infection, corresponding to 5% mortality. The virus was shed daily in the faeces of infected chickens, and was found distributed in multiple organs. Macroscopic and microscopic lesions in the kidneys were observed. This is the first paper that describes the genomic characteristics and pathogenicity of a novel ANV strain in China. RESEARCH HIGHLIGHTS: A novel ANV strain was isolated for the first time from diseased broilers in China. The ANV strain caused nephritis and 5% mortality rate in 1-day-old SPF chickens.